Χωρική ανάλυση γεωχημικών δεδομένων από το γεωχημικό άτλαντα της Κύπρου στην επαρχία Λευκωσίας - Μαυρουδή, Θεοχάρια (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
This dissertation aims to present the geochemical Atlas of Cyprus, an attempt of several years by the Geological Survey Department in Cyprus with the help of University of New South Wales. The Geology, Geomorphology and as well as the Tectonic evolution of Cyprus are also presented in this project showing important role in the geochemistry of the island's soil. Geoinformatics and Geospatial Technologies are also associated with geochemistry, and through Geographic Information Systems (GIS) it can be demonstrated with the help of interactive maps the dispersion of specific elements we found in the soil, whether it is a top soil or sub soil. Precisely this dissertation presents the distribution of three elements of copper, cobalt and manganese. The results of the dispersion are demonstrated by maps generated by spatial interpolation.
Keywords: Geochemistry; Geochemical map; Geoinformations; Cyprus; Soil; Γεωχημεία; Γεωχημικός άτλαντας; Γεωπληροφορική; Κύπρος; Έδαφος